Intranasal delivery of mesenchymal stem cell‐derived extracellular vesicles exerts immunomodulatory and neuroprotective effects in a 3xTg model of Alzheimer's disease. (4th June 2020) - Losurdo, Morris; Pedrazzoli, Matteo; D'Agostino, Claudia; Elia, Chiara A.; Massenzio, Francesca; Lonati, Elena; Mauri, Mario; Rizzi, Laura; Molteni, Laura; Bresciani, Elena; Dander, Erica; D'Amico, Giovanna; et al.
Abstract: The critical role of neuroinflammation in favoring and accelerating the pathogenic process in Alzheimer's disease (AD) increased the need to target the cerebral innate immune cells as a potential therapeutic strategy to slow down the disease progression. In this scenario, mesenchymal stem cells (MSCs) have risen considerable interest thanks to their immunomodulatory properties, which have been largely ascribed to the release of extracellular vesicles (EVs), namely exosomes and microvesicles. Indeed, the beneficial effects of MSC‐EVs in regulating the inflammatory response have been reported in different AD mouse models, upon chronic intravenous or intracerebroventricular administration. In this study, we use the triple‐transgenic 3xTg mice showing for the first time that the intranasal route of administration of EVs, derived from cytokine‐preconditioned MSCs, was able to induce immunomodulatory and neuroprotective effects in AD. MSC‐EVs reached the brain, where they dampened the activation of microglia cells and increased dendritic spine density. MSC‐EVs polarized in vitro murine primary microglia toward an anti‐inflammatory phenotype suggesting that the neuroprotective effects observed in transgenic mice could result from a positive modulation of the inflammatory status. The possibility to administer MSC‐EVs through a noninvasive route and the demonstration of their anti‐inflammatory efficacy might accelerate the chance of a translational exploitation of MSC‐EVs in AD. Abstract : In a preclinical model of Alzheimer's disease, characterized by neuronal damage and a high rate of inflammation (left), the intranasal (IN) administration of extracellular vesicles (EVs) derived from mesenchymal stromal/stem cells (MSCs) operates in dampening inflammation (by reducing microglia activation) and in inducing neuroprotective effects (by decreasing spine loss) (right). These data suggest the possibility that the IN route administration of MSC‐EVs might accelerate the chance of a translational exploitation of MSC‐EVs toward therapy.